Metaproteomics of Microbiota in Naturally Fermented Soybean Paste, Da‐jiang. Issue 5 (18th April 2018) - Zhang, Ping; Zhang, Pengfei; Xie, Mengxi; An, Feiyu; Qiu, Boshu; Wu, Rina
Abstract : Abstract: Da‐jiang is a typical traditional fermented soybean product in China. At present, the proteins in da‐jiang are needed to be explored. The composition and species of microbial proteins in traditional fermented da‐jiang were analyzed by metaproteomics based on sodium dodecyl sulfonate‐polyacrylamide gel electrophoresis (SDS‐PAGE) and liquid chromatography‐mass spectrometry/mass spectrometry (LC‐MS/MS). The results showed that the number and variety of microbial proteins in the traditional fermented da‐jiang from different regions were different. The production site influences the fermentation in da‐jiang . Then we analyzed the functions of the microbial proteins identified in da‐jiang, and found that they were mainly involved in the process of protein synthesis, glycometabolism and nucleic acid synthesis. In addtion, we compared the proteins composition in different da‐jiang . There are 51 common proteins of naturally fermented da‐jiang, and 25 common microbial sources. The main commonly microbial sources of fungal proteins are Saccharomyces cerevisiae and Schizosaccharomyces ; the main commonly microbial sources of bacterial proteins are Enterococcus faecalis, Leuconostoc mesenteroides, Acinetobacter baumannii, and Bacillus subtilis . These common microbes play the predominant role in da‐jiang fermentation. The present results help us to understand the fermentation of da‐jiang and improve the quality and safety of final products in the future. Practical Application: The study illustrated metaproteome of microbiota in traditional fermented soybean paste, da‐jiang, by sodium dodecyl sulfonate‐polyacrylamide gel electrophoresis (SDS‐PAGE) and liquid chromatography‐mass spectrometry/mass spectrometry (LC‐MS/MS). A method of extracting metaproteome from microbiota in da‐jiang was attempted. The findings help to understand the fermentation of da‐jiang and improve the quality and safety of da‐jiang in fermented industry.